Inshore-offshore distribution of larval fishes in Lake Superior off the western coast of the Keweenaw Peninsula, Michigan - Oyadomari, Jason K.; Auer, Nancy A. (Journal of Great Lakes Research, 2004)
We surveyed the larval fish community in Lake Superior off the western coast of the Keweenaw Peninsula, Michigan, as a first component in understanding how the Keweenaw Current affects larval fish distribution and survivorship. On transects at Ontonagon, Houghton, and Eagle Harbor, we collected larval fishes with a 1-m diameter plankton net towed through surface and deep (below metalimnion) waters at an inshore location (1 km from shore) and an offshore location (5-9 km from shore) during day and night in 1998 and 1999. The most abundant larvae caught were lake herring (Coregonus artedii), rainbow smelt (Osmerus mordax), burbot (Lota lota), deepwater sculpin (Myoxocephalus thompsoni), and spoonhead sculpin (Cottus ricei). Lake herring was generally most abundant at the surface during the day, while the other four species avoided the surface by day but not at night. Overall, larval fish density was greater inshore than offshore, with exceptions for particular locations and seasonal periods (1.24x for lake herring, 12.93x for rainbow smelt, 1.27x for burbot, 1.25x for deepwater sculpin, and 4.26x for spoonhead sculpin). Differences in the sizes of larvae between inshore and offshore locations, in conjunction with density patterns, suggest a seasonal inshore to offshore movement. Despite the presence of the Keweenaw Current, the overall distribution patterns of larval fishes follow those of previous studies conducted in the Great Lakes, but with lower densities.